How kindergarten came to America : Friedrich Froebel's radical vision of early childhood education - Von, Bertha (The new press, 2007)
Originally published: Reminiscences of Friedrich Froebel. Boston : Lee & Shepard,1877. Translated from the German; Originally published as Reminiscences of Friedrich Froebel, this enchanting 1894 account of the German inventor of kindergartens was instrumental in bringing kindergartens to the United States. This lively portrait of a pioneer of modern education is a refreshing reminder of the essential role of play and creative exploration in the development of children. Froebel's methods provide a much-needed antidote to the current emphasis on high-stakes testing and accelerated curricula—a corruption, as Herbert Kohl argues in his foreword, of the original concept of kindergartens as children's gardens of learning